2023
DOI: 10.3390/md21050282
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies to Extract Fucoxanthin from Undaria pinnatifida: Microwave vs. Ultrasound Assisted Extractions

Abstract: Macroalgae are an extensive resource for the obtention of bioactive compounds, mainly phenolic compounds, phlorotannins, and pigments. Fucoxanthin (Fx) is the most abundant pigment present in brown algae and has shown several useful bioactivities that can be used to fortify products in the food and cosmetic industries. Nevertheless, to date, there is still insufficient literature reporting on the extraction yield of Fx from U. pinnatifida species from green technologies. In this regard, the present study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Heating is the most extensively studied factor influencing fucoxanthin extractability and stability. Some studies have found that temperature has a significant effect on fucoxanthin recovery using pressurized-liquid extraction and microwave-assisted extraction from different macro-and microalgae species [5,6]. Fucoxanthin extractability increases as temperature increases up to a certain value (around 100 • C, depending on species).…”
Section: Heat Processingmentioning
confidence: 99%
“…Heating is the most extensively studied factor influencing fucoxanthin extractability and stability. Some studies have found that temperature has a significant effect on fucoxanthin recovery using pressurized-liquid extraction and microwave-assisted extraction from different macro-and microalgae species [5,6]. Fucoxanthin extractability increases as temperature increases up to a certain value (around 100 • C, depending on species).…”
Section: Heat Processingmentioning
confidence: 99%
“…Based on the principles of this technology, several parameters, such as solid liquid ratio, temperature, frequency and power, must be defined in an experimental work to achieve the desired product [20]. Lourenço-Lopes and coauthors (2023), focusing on the extraction of fucoxanthin, the main pigment in brown algae, explored ultrasound-assisted extraction and microwave-assisted extraction to obtain this valuable fraction from Undaria pinnatifida [21]. Based on the biorefinery concept, several fractions with potential research interests can be obtained from brown seaweeds [22].…”
Section: Introductionmentioning
confidence: 99%